2017
DOI: 10.1115/1.4036081
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Basic Approaches to Numerical Modeling of Phase Change Problems—Accuracy, Efficiency, and Parallel Decomposition

Abstract: The fast and accurate modeling of phase change is of a significant importance in many processes from steel casting to latent heat thermal energy storage. The paper presents a numerical case study on the transient 3D heat diffusion problem with phase change. Three different approaches to modeling of the solid–liquid phase change in combination with four commonly used numerical schemes are compared for their efficiency, accuracy, applicability, simplicity of implementation, and robustness. The possibility of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…where ∆H is the latent heat (J/kg) and f s is the solid fraction (-). The Enthalpy method was used for modelling the solidification process, see Mauder et al [10]. The Enthalpy method is robust method because it ensures energy conservation and there is no discontinuity at either the liquidus or the solidus temperatures because the solidification/melting path is characterized strictly by decreasing/increasing enthalpy.…”
Section: Solidification Model-brdsmmentioning
confidence: 99%
See 3 more Smart Citations
“…where ∆H is the latent heat (J/kg) and f s is the solid fraction (-). The Enthalpy method was used for modelling the solidification process, see Mauder et al [10]. The Enthalpy method is robust method because it ensures energy conservation and there is no discontinuity at either the liquidus or the solidus temperatures because the solidification/melting path is characterized strictly by decreasing/increasing enthalpy.…”
Section: Solidification Model-brdsmmentioning
confidence: 99%
“…There are several discretization schemes how to solve the Equations (1)- (7). After large-scale numerical studies two numerical schemes proved to be good candidates for solving the case of 3-D transient heat transfer problem with solidification phenomena, Simple Explicit (SE) and Alternating Direction Implicit (ADI), see Mauder et al [10]. The ADI scheme proposed by Douglas and Gunn is unconditionally stable and retains the second-order accuracy when applied to 3-D problems.…”
Section: Numerical Formulation and Massive Parallelizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Which solver performed best depended on the time step and mesh resoluti Tamma and Namburu [13] analyzed explicit and implicit enthalpy methods for the fin element method; they found that the explicit methods are faster since no update of mass matrix is necessary. Mauder et al [14] compared different methods in MATLAB accuracy, simulation time, and the applicability of parallelization. They stated that effectiveness of the methods depends on the problem under study.…”
Section: Introductionmentioning
confidence: 99%